Asset Proportions in Optimal Portfolios - Hadar, Josef; Seo, Tae Kun (Review of Economic Studies, 1988)
The paper is concerned with conditions under which the proportion of a given asset in the optimal portfolio of a risk averse agent is at least as large as some given proportion. The paper provides a condition that is necessary and sufficient for such a result to hold. The analysis is then confined to portfolios in which the distributions of assets differ by either a first-degree stochastic dominance shift or by a mean-preserving shift. Examples are provided to show that under some conditions a risk averter may invest a smaller proportion of his wealth in the dominating asset than in the dominated asset. The paper then provides conditions that are necessary and sufficient for a risk averter to invest more in the dominating asset.